The Relationship Between Self-Efficacy on Teaching Reading Comprehension Skills among Secondary Schools Teachers in Telangana State, India: Hubungan Antara Self-Efficacy pada Pengajaran Keterampilan Pemahaman Membaca di antara Guru Sekolah Menengah di Telangana State, India - Begum, Farhath Unissa; Hamzah, Mohd Hilmi Bin (Universitas Muhammadiyah Sidoarjo, 2018)
Over the years, the quality and effectiveness of teaching have been the priority of the Indian government in improving the education sector, particularly the teaching reading comprehension skill among teachers. This paper investigates the relationship between self-efficacy on teaching reading comprehension skills among secondary school teachers in Telangana State, India. The study is a quantitative research of the survey type. The total of 2019 teachers of government owned secondary schools constituted the population, simple random sampling technique was used to select 192 teaching English language across all secondary schools in the state. Two sets of questionnaire title Teacher self-efficacy Scale (TSES) and Teaching Reading Comprehension Skills which was adapted from Progress International Literacy Study (PIRLS) were used to seek information from English teachers. Pearson product moment correlation statistics was used to analysis the data and the results of the findings revealed that there is a statistically significant relationship between self-efficacy and teaching reading comprehension skill among secondary school teachers in Telangana State India. Therefore, this study recommends that the school management should implement a policy that will increase teacher efficacy to improve students reading comprehension and to design more effective reading course and activities in the classroom.